(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article supplies analysis of the area of organic agricultural lands in the world and Ukraine. The research confirms almost twice growth of the mentioned index for the period of 2010-2017 in the world. In 2017, the figure was 69.8 million hectare. However, in Ukraine the index has increased 1.6 times in the same period and constitutes421500 hectares. It is argued that the highest share of organic agricultural lands in the total structure of the country is marked in Uruguay, i.e. 7.42 %; in Italy, it is a little lower one and constitutes 4.95 % and in Spain – 3.89 %; while the lowest index is in China – 0.17 %. In Ukraine, the index takes 0.68 %. The work confirms a positive dynamics of growth of the number of enterprises, engaged in production of organic products in Ukraine. However, that positive dynamics is far from the world indices. The research determines main problems of development in the field of organic production and sale of productions. The article stresses the necessity to improve regulatory support for organic production, because there is no legally approved uniform interpretation of the concept of “organic arable farming”, while arable farming is the basis for organic production. The authors of the work ground the necessity of control for the process of production of organic products, point a poor assortment and insufficient amount of biological means of plant protection. One observes little application and practical use of resource-saving technologies, inappropriate conditions for products storage, forcing the necessity of urgent solution of those problems. Generally, it will improve the indices of production and sale of organic products. However, it will not much approach the world market tendencies.